Pelatihan Penggunaan Alat Peraga terhadap Hasil Pembelajaran Matematika pada Siswa Sekolah Dasar - Iza Azkia Rahma Wijaya; Ismi Widyaningrum; Arina Nur Indriani; Rihatul Jannah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Training is a concept that aims to improve the knowledge and skills of someone who has experienced rapid and modern development. Props are objects that can be used to help teachers describe or explain subject matter to students. The training model is carried out starting from observation. The first stage is interviews with teachers and students to analyze learning styles and student characteristics. The props are loaded in the form of a protractor as media to be used in mathematics learning activities. Arc-shaped teaching aids are effective in helping them draw more easily, and they can also determine corner points and corner legs in learning mathematics.